The managerial and economic effects of celebrity endorsement on consumer purchasing intentions - Pereira, H. G. (2016)
Despite the fact that celebrity endorsement brings up some risks, it has been used quite extensively in the present era and it is a method to reach competitive advantage by companies. The economic effects for companies are obvious. This study focuses on examining the relationship between a set of variables (gender, credibility, attractiveness, type, multiple endorsements and multiple product endorsement) that were identified during the literature review as characteristics of the TV advertisings and consumers purchasing intentions. A questionnaire survey was applied. This study is based on a sample of 285 young respondents. Respondents answered two sets of questions after viewing an advertisement of a specific product featuring one or more endorsers. A quantitative approach has been adopted to investigate the relationship between the purchase intentions and the perceptions of the six characteristics of celebrity endorsement mentioned above. Results revealed that all the characteristics of celebrity endorsement analyzed had a positive impact in consumers purchasing intentions, however some of them were quite low. This study has an approach with relevant consequences for companies, either economic or managerial, bringing room to analyze and to discuss the related coming up managerial implications.